2016
DOI: 10.1016/j.chom.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of the Gut Microbiome in UK Twins

Abstract: Summary Studies in mice and humans have revealed intriguing associations between host genetics and the microbiome. Here we report a 16S rRNA-based analysis of the gut microbiome in 1,126 twin pairs, a subset of which was previously reported. Tripling the sample narrowed the confidence intervals around heritability estimates and uncovered additional heritable taxa, some of which are validated in other studies. Repeat sampling of subjects showed heritable taxa to be temporally stable. A candidate gene approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
875
5
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 875 publications
(965 citation statements)
references
References 85 publications
45
875
5
6
Order By: Relevance
“…An analysis of 127 Hutterites reported several heritable taxa [39], but the statistical significance of these results after multiple testing correction has not been reported. Additionally, several recent studies have identified a significant heritability of bacterial α-diversity [28,30,39]. In contrast, a recent analysis of 1,046 Israeli individuals from different ancestral origins but a relatively shared environment did not replicate any of the above results, and did not identify statistically significant host-genomics associations with either the overall microbiome composition or individual taxa [8].…”
Section: Limited Evidence For Gut Microbiome-host Genotype Associatiomentioning
confidence: 70%
See 4 more Smart Citations
“…An analysis of 127 Hutterites reported several heritable taxa [39], but the statistical significance of these results after multiple testing correction has not been reported. Additionally, several recent studies have identified a significant heritability of bacterial α-diversity [28,30,39]. In contrast, a recent analysis of 1,046 Israeli individuals from different ancestral origins but a relatively shared environment did not replicate any of the above results, and did not identify statistically significant host-genomics associations with either the overall microbiome composition or individual taxa [8].…”
Section: Limited Evidence For Gut Microbiome-host Genotype Associatiomentioning
confidence: 70%
“…However, a potential shortcoming of the above studies is that they require previous knowledge of associated genes, and thus cannot discover new associations. Thus, recent studies have performed unbiased microbiome-genome wide association studies (mGWAS) spanning 93-1,812 individuals [8,[27][28][29][30][31].…”
Section: Limited Power Of Microbiome Genome Wide Association Studiesmentioning
confidence: 99%
See 3 more Smart Citations